The latest recommendations of the Polish Diabetes Association and the American Diabetes Association in the treatment of diabetes with modern drugs - Szymon Marosz; Aleksandra Borkowska; Paulina Mikulska; Katarzyna Borkowska; Jolanta Kowieska (Kazimierz Wielki University, 2020)
Introduction: Diabetes is a global problem, affecting nearly 422 million people around the world. Pathogenesis includes a defect in secretion or insulin activity. This results in an increase in the glucose level, which is associated with the development of complications. These include changes in peripheral vessels and nerves that lead to their damage. It is necessary to introduce appropriate treatment in the earliest stages of the disease to prevent these effects. Materials and methods: The aim of this work is to present knowledge about the treatment based on the recommendations of the Polish Diabetes Association, American Diabetes Association, as well as a literature review and analysis of publications published on PubMed and Google Scholar platforms. Results: Over the years, the recommendations and recommendations for treatment change. Recently, a greater role has been given to the latest antidiabetic drugs. This group includes SGLT-2 inhibitors as well as incremental drugs, the main representatives of which are GLP-1 analogues. These drugs affect the level of glycemia, but also have a beneficial effect on weight reduction and reduce the risk of cardiovascular events. Recently, Poland has introduced reimbursement of some new generation antidiabetic drugs such as dapaglyphosin, empaglyphosin and canaglyphosin. Conclusions: Dynamic development of diabetes treatment helps to slow down the course of the disease and postpones the introduction of insulin therapy as the final treatment method. Reimbursement of some antidiabetic drugs enables patients to have better access to drugs that have not been within their reach so far. The changes introduced are, in a way, groundbreaking in the treatment of diabetes.